Interactive Nutrition Education Using Animated Videos and Puzzles Improves Fruit and Vegetable Nutrition Knowledge Among Elementary School Children - Arum Dinar Denta Listya; Dewi Sari Rochmayani (Universitas Negeri Semarang, 2026)
Background: Low consumption of fruits and vegetables in elementary school children is at risk of causing health and nutrition problems in the future, one of which is due to lack of nutritional knowledge. Nutrition education from an early age is needed as a preventive effort, and the use of interactive media such as animated videos and puzzles is considered effective in increasing children's understanding of the importance of fruit and vegetable consumption. The purpose of this study is to analyze the effectiveness of nutrition education through interactive media in the form of animated videos and puzzles on the knowledge of fruit and vegetable consumption in elementary school children. Methods: The study used a quasi-experimental design with a pretest-posttest non-equivalent control group design. The 54 students were divided into experimental and control groups. The experimental group was educated using animated videos and puzzles, while the control group used the lecture method. Data analysis used Independent Sample t-Test, Paired Sample t-Test and N-Gain test. Results: Results showed a significant increase in knowledge in the experimental group (p = 0.000) compared to the control (p = 0.054), with moderate effectiveness based on the N-Gain value (0.5854 or 58.54%). Conclusion: Nutrition education with interactive media of animated videos and puzzles is effective in significantly increasing the knowledge of fruit and vegetable consumption in elementary school children, and can be an interesting educational strategy and in accordance with the learning characteristics of children of that age.